Phenomenon of Supply Chain Resilience, Company Performance, and Competitive Advantage in Shopee E-commerce Sellers: A Phenomenological Study - Harahap, Lokot Muda; Ginting, Rika Manda Sary Br; Harahap, Putri Khoirun Nisa; Ginting, Anis Sonia Br; Fadillah, Nisa; Syafira, Tanya Ananda (Lembaga Riset Mutiara Akbar (LARISMA), 2023)
This study aims to explore the phenomenon of supply chain resilience, company performance, and competitive advantage in Shopee e-commerce sellers through a phenomenological approach. Based on in-depth interviews, field observations, and literature reviews, it is concluded that supply chain resilience has a positive influence on company performance and competitive advantage for Shopee e-commerce sellers. Sellers with resilient supply chains are able to increase sales, customer satisfaction, and business growth, as well as maintain competitive advantage through reliable service, faster delivery times, and consistent product availability. Key factors contributing to supply chain resilience in the context of e-commerce include strong collaboration and communication with suppliers and business partners, adoption of digital technology in supply chain management, and flexibility and agility in responding to demand fluctuations and supply chain disruptions. These findings confirm the importance of supply chain resilience for e-commerce sellers in facing challenges such as demand fluctuations, logistics issues, and intense competition. Sellers with strong supply chain resilience can continue to operate and expand their businesses despite disruptions. This study provides new insights into how e-commerce sellers in Indonesia implement strategies to improve their supply chain resilience, as well as its impact on company performance and competitive advantage.